Reviews on Calcium Mediated Secondary Messengers in Chronic Opioids Exposure/Addiction - Ibrahim H Sani, Maryam I Umar, Nasir Mohamad, U.S. Mahadeva Rao, R. Mohd Adzim Khalili, Nor Hidayah Abu Bakar (Journal of Applied Pharmaceutical Science, 2015)
Addiction and withdrawal are problems disturbing the health of the individual and also causes difficulties for society, raising the rates of divorce, unemployment and government spending on legal and medical systems. Opioids show an important pharmacological effect in the treatment of pain, with extremely addictive potential. Chronic opioid exposure is known to produce the complex behaviors of tolerance and dependence, a state exposed by opioid abstinence leading to withdrawal syndrome, as well as oxidative stress. Studies show that calcium mediated secondary messengers play a crucial role in the mechanism of addictive process and oxidative stress induced by chronic opioid usage. Calcium/calmodulin-dependent protein kinase II (CaMKII), is a major calcium regulated signal transducer that controls many neuronal systems and play important role in neuronal plasticity and can act as a key and direct promoting opioid tolerance and dependence and identifying such a direct mechanism may be useful for designing a pharmacology treatment for these conditions, recent studies, has been shown that calcium channels antagonist can be used in the treatment of withdrawal syndrome. Chronic opioid exposure associated with tolerance, dependence withdrawal syndrome and oxidative stress. Studies has shown that calcium mediated secondary messengers involved in the genesis of these conditions, better understanding of biological mechanisms underlie reduction in neuronal cell excitability could help in the identification of pharmacological targets for treatment.
Keywords: Calcium,Calmodulin, Opioid, Oxidative stress,Neuronal cell.